The Impact of Financial Risks on the Performance of Insurance Companies Listed in Amman Stock Exchange (ASE) - Soda, Mohammed Zakaria; Alkhalaileh, Taghreed Ahmad (Jordan Journal of Business Administration, 2025)
This study aimed to find out the impact of financial risks on the performance of insurance companies listed in Amman Stock Exchange. Multiple regression equation was used, and the study population consisted of (22) Jordanian insurance companies listed in Amman Stock Exchange (ASE) for the period (2017-2021). The most important results of the study showed that there is an impact of financial risks represented by (underwriting risks, liquidity risks, and capital risks) on the profitability of shares, and on the return on assets in the insurance companies listed in Amman Stock Exchange, and there’s no impact of financial risks represented by (underwriting risks, liquidity risks, and capital risks) on the return on equity. The results of regression coefficients showed that there is no effect of the size of the company as a control variable on the profitability of shares and on the return on assets, while it had an impact on the return on equity. The study recommended the necessity for Jordanian insurance companies’ managements to conduct sufficient studies to investigate the internal and external financial risks to achieve greater profits and thus maximize the wealth of the owners, as well as the need for disclosure by the Jordanian insurance companies about financial risks, because they are closely related to investment decisions, and providing sufficient information to assess risks and thus make appropriate decisions.